Human Reseources Management at Charitas Nandan Elementary School and Mangunan Experimental Elementary School in Yogyakarta - Salupra, Fransiska; Sujarwo, Sujarwo (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This study aims to describe (1) human resource management; (2) obstacles experienced in human resource management is teachers and school administrative personnel; and (3) factors influencing human resource management at Karitas Nandan and Eksperimental Mangunan Elementary School in Yogyakarta..This study used a descriptive qualitative research approach. The subjects of this research were principals, vice principals, teachers, and school administration personnel. Data collection techniques used observation, interviews, and documentation. Qualitative research is research with the main instrument in collecting data is the researcher himself with the help of observation guidelines, interview guidelines, and documentation guidelines. Furthermore, the data analysis stage was carried out by collecting data, condensing data, presenting data and drawing conclusions. The results showed that (1) human resource management at Karitas Nandan and Eksperimental Mangunan Elementary School in Yogyakarta includes planning, recruitment, selection, placement and organization, training and development, maintenance and dismissal. (2) the obstacles experienced are limited communication, mismatch of teachers with their fields, limited HR competence, excessive workload, the existence of Merdeka Belajar platform which results in difficulties in realizing school distinctiveness, and changing school policies. (3) influencing factors include finance, motivation, age, and individual or group dynamics to find a suitable pattern in accordance with the Romo Mangun Education concept